Comparative antibacterial and antifungal activities of sulfur nanoparticles capped with chitosan. (July 2020) - Kim, Yeon Ho; Kim, Geun Hyang; Yoon, Ki Sun; Shankar, Shiv; Rhim, Jong-Whan
Abstract: The antimicrobial activity of sulfur nanoparticles (SNPs) was compared with elemental sulfur and sulfur-containing salts (sodium thiosulfate and sodium metabisulfite) against bacteria ( Escherichia coli, Staphylococcus aureus ) and fungi ( Aspergillus flavus, Candida albicans ) using the paper disc, broth microdilution, and time-kill assay methods. The results of the paper disc and MIC tests showed stronger antimicrobial activity of SNPs compared to the elemental sulfur and sulfur-containing salts. SNPs showed more potent activity against bacteria than fungi. Among the test microorganisms, E. coli (Gram-negative) was the most susceptible to SNPs, followed by S. aureus (Gram-positive), C. albicans (yeast), and A. flavus (mold). Scanning electron micrographs of microorganisms treated with SNPs showed different cell disruption patterns depending on the type of microorganisms. Graphical abstract: Image 1 Highlights: Chitosan-capped sulfur nanoparticles (SNPs) were prepared by the reduction of sodium thiosulfate. Antimicrobial activity of SNPs was compared with elemental sulfur and S-containing salts. Agar diffusion, MIC/MBC(MFC), time-kill assay for bacteria and fungi were determined. SNPs showed stronger antibacterial and antifungal activity than elemental S and S-salts.